Biomechanical, physiological and perceptual responses of three different athlete groups to the cycle-run transition - Cripwell, Devin Matthew (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2011)
The transition from cycling to running has been identified as one of the key determinants of success in triathlon, as it has been suggested that the cycle may affect subsequent running efficiency such that running performance is significantly altered or reduced. It is also suggested that athletes more adapted to the transition itself, rather than purely running or cycling, may be more efficient during the post-cycle running bout. The current study sought to investigate the effects of prior cycling on subsequent selected biomechanical, physiological and perceptual responses of three different athlete groups. Subjects were selected on the basis of their sporting background, and were divided into three groups "“ triathletes, cyclists and runners. Experimentation required subjects to perform a seven minute treadmill running protocol at 15km.hâ »Â¹, during which biomechanical (EMG, Stride rate, Stride length, Vertical acceleration), physiological (HR, VOâ‚‚, EE) and perceptual (RPE) responses were recorded. After resting, subjects were required to perform a twenty minute stationary cycle at 70% of maximal aerobic power (previously determined), immediately followed by a second seven minute treadmill running protocol during which the same data were collected and compared to those collected during the first run. Biomechanical responses indicate that the cycle protocol had no effect on the muscle activity or vertical acceleration responses of any of the three subject groups, while the triathlete group significantly altered their gait responses in order to preserve running economy. The triathlete group was the least affected when considering the physiological responses, as running economy was preserved for this group. The runner and cyclist groups were significantly affected by the transition, as running economy decreased significantly for these groups. Perceptual responses indicate that athletes more experienced with the transition may find the transition from cycling to running to be easier than those inexperienced in this transition. It is apparent that a high intensity cycle protocol has limited statistical impact on selected biomechanical responses, while physiological and perceptual responses were altered, during a subsequent run, regardless of athlete type. That said, the ability of transition-trained athletes to transition comfortably between disciplines was highlighted, which may have important performance implications.
Keywords: Biomechanics -- Research; Human mechanics -- Research; Cycling -- Physiological aspects -- Research; Running -- Physiological aspects -- Research; Exercise -- Physiological aspects -- Research